Stock Investment Risk Analysis Using the Value at Risk (VAR) Method - Siti Aisyah; Abdul Wahab; Marjono; Prayetno; Nicholas Renaldo (LP2M IAIN Palopo, 2026)
This study aims to analyze stock investment risk using the Value at Risk (VaR) method with a qualitative approach. The main focus of the study is to understand how investors interpret risk and how the VaR concept is understood and applied in investment decision-making practices. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants in this study were selected through purposive sampling, namely stock investors who have experience in investment activities and a basic understanding of risk. Data analysis was conducted using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, with data validity maintained through triangulation and member checks. The results show that most investors have recognized the importance of risk in stock investment, but understanding of the Value at Risk (VaR) method is still uneven. Investors with a financial background tend to better understand and utilize VaR in determining risk tolerance limits and investment strategies, while other investors rely more on an intuitive approach. There is a gap between the theoretical concept of VaR and its implementation in the field, caused by the complexity of the calculation, limited financial literacy, and psychological factors such as emotions and speculative behavior. Nevertheless, VaR still holds significant potential as a risk management tool if supported by adequate understanding and the use of financial technology. In conclusion, the application of the Value at Risk (VaR) method in stock investment is still suboptimal, but it has high relevance in helping investors manage risk more measurably. This research contributes to the understanding of risk management practices from an investor behavioral perspective and emphasizes the importance of integrating technical and psychological approaches in investment decision-making.